Decorations in Ahmed Pasha Al Qarmanli Mosque - Mohamed Khalifa Eblao, Amira; Abdul Hamid, Faisal @ Ahamad Faisal (Journal Al-Muqaddimah, 2017)
The decoration evolved over the ages and took forms and patterns characterized by each civilization from the previous civilization, until the emergence of the Islamic religion and spread in various countries and continents and came to give the decorations on the Islamic civilization in general and Islamic. Art In particular, since the distinctive function of Islamic art is the beauty industry, it is one of the means and methods that enable us to make beauty, the area that connects the general form and content to be with each other a cohesive unit according to the disciplines and teachings of the Islamic religion. Hence, this article attempts to delve into the decorations and decorative designs of different types of plants, engineering and writing, used in the mosque Ahmed Pasha Al-Qurmani through: − About Ahmad Pasha Al - Qarmani Mosque − Types of decorations used in the mosque − Materials used in decoration All of these points will be addressed through the decorations at Ahmed Pasha Mosque in the Libyan city of Tripoli. Through the analytical descriptive approach, we try to reach the most important Islamic disciplines that must be followed in the decoration of religious buildings. The result is that the decorative designs of different types are closely related to the Islamic disciplines and characteristics Distinguishing them from the rest of the other arts, through which religious teachings can be disseminated in artistic ways